Dosage Effects of Fadrozole on Growth and Development of Sex-Reversed Genetic Female Chickens - Xiu-rong YANG; He-sheng JIANG; Jiang-xia ZHENG; Lu-jiang QU; Si-rui CHEN; Jun-ying LI; Gui-yun XU; Ning YANG (Journal of Integrative Agriculture, 2013)
Fadrozole, an aromatase inhibitor, can masculinize genetic female chickens and high-dose decreases the hatchability. Therefore, it is important to study the growth and development of sex-reversed females after hatch. Chick embryos from a population of CAU3 egg-type were treated with different concentrations of Fadrozole prior to the sexual differentiation at E3.0 (st18). At hatch, the phenotypic sex and genetic sex were identified by vent sexing and genetic diagnosis with CHD1, respectively. Body weight and shank length of sex reversal were tested at 8 and 20 wk, respectively. Testicular development, oviduct and ovarian degeneration were observed and serum concentration of estradiol and testosterone were tested with radioimmunoassay (RIA) at 30 wk. The results showed that body weight and shank length of sex-reversed females were not significantly different between low-dose groups (0.1, 0.3, and 0.5 mg for F1, F2, and F3, respectively) and high-dose groups (1.0 and 1.3 mg for F4 and F5, respectively) (P>0.05). Left and right testes or ovotestes in F2, F3, F4, and F5 groups were heavier than that of in F1 group (P<0.05). While the gonad weight of treatment groups were less than that in male control (P<0.05), oviduct weight in F2, F3, F4, and F5 groups were significant differences compared with female control and F1 group (P<0.05). Egg number from onset of laying egg to 30 wk in F4 and F5 groups were less than in female control, F1 and F2 groups (P<0.05). Serum testosterone level in F5 group was significant higher compared with female control, F1, F2, F3, and F4 groups (P<0.05), but significant lower compared with male control (P<0.05). While concentration of serum estradiol in F5 group was significant lower compared with female control, F1, F2, and F4 groups (P<0.05). In conclusion, the concentration of Fadrozole do not affect postnatal growth of sex-reversed female chicken and the degree of sex-reversed females elevate with the increase of Fadrozole concentration at sex maturity.